Reinforcing properties of fencamfamine: Involvement of dopamine and opioid receptors - Da Silva Planeta, Cleopatra [UNESP]; Aizenstein, Moacyr Luiz; DeLucia, Roberto (Elsevier, 1995)
Fencamfamine (FCF) is a psychostimulant classified as an indirect dopamine agonist. The conditioning place preference (CPP) paradigm was used to investigate the reinforcing properties of FCF. After initial preferences had been determined, animals were conditioned with FCF (1.75, 3.5, or 7.0 mg/kg; IP). Only at the dose of 3.5 mg/kg FCF produced a significant place preference. Pretreatment with SCH23390 (0.05 mg/kg, SC) or naloxone (1.0 mg/kg SC) 10 min before FCF (3.5 mg/kg; IP) blocked both FCF-induced hyperactivity and CPP. Pretreatment with metoclopramide (10.0 mg/kg; IP) or pimozide (1.0 mg/kg, IP), respectively, 30 min or 4 h before FCF (3.5 mg/kg; IP), which blocked the FCF-induced locomotor activity, failed to influence place conditioning produced by FCF. In conclusion, the present study suggests that dopamine D 1 and opioid receptors are related to FCF reinforcing effect, while dopamine D 2 subtype receptor was ineffective in modifying FCF-induced CPP.
Keywords: Dopamine receptors; Fencamfamine; Opioid receptors; Place conditioning; Reinforcement; 8 chloro 2,3,4,5 tetrahydro 3 methyl 5 phenyl 1h 3 benzazepin 7 ol hydrogen maleate; dopamine 1 receptor; dopamine 2 receptor; dopamine receptor; dopamine receptor stimulating agent; fencamfamin; metoclopramide; naloxone; opiate receptor; pimozide; psychostimulant agent; receptor subtype; animal experiment; conditioning; controlled study; drug antagonism; hyperactivity; intraperitoneal drug administration; nonhuman; place preference; priority journal; rat; reinforcement; subcutaneous drug administration; Animal; Binding, Competitive; Central Nervous System Stimulants; Conditioning, Operant; Metoclopramide; Naloxone; Norbornanes; Pimozide; Rats; Receptors, Dopamine D1; Receptors, Dopamine D2; Receptors, Opioid, mu; Reinforcement (Psychology); Sch-23390; Animalia